Implementasi Program Kesehatan Ibu dan Anak (Kia): Studi Kasus di Puskesmas Suro Makmur Kabupaten Aceh Singkil Tahun 2025 - Adinda Febi Zahra; Basri Aramico; Mira Gusweni (Yayasan Literasi Sains Indonesia, 2025)
The Maternal and Child Health (MCH) Program is a priority for reducing maternal and child mortality and improving public health. This study aims to evaluate the implementation of the MCH Program at the Suro Makmur Community Health Center (Puskesmas) in Aceh Singkil in 2025. The method used was a qualitative case study conducted between July 3-11, 2025. Primary data was collected through in-depth interviews with the Head of the Community Health Center, the person in charge of the MCH program, implementing midwives, integrated health post (Posyandu) cadres, and six mothers from the target group. Secondary data was drawn from Community Health Center documents. The analysis focused on input, process, and output aspects using normative, empirical, and gap analysis approaches. The results indicate that the MCH policy refers to the Health Office and central regulations. Human resources are adequate, but distribution and training are suboptimal. The MCH service process is structured, but obstacles arise from budget and infrastructure limitations. In terms of output, program achievements have not met targets, the quality of outreach is low, and community participation is influenced by culture, distance, and trust in health workers. In conclusion, the implementation of the MCH Program at the Suro Makmur Community Health Center (Puskesmas) was optimal, despite a gap between standards and field practice. This study provides important insights for improving the implementation of the MCH program at the community health center level to support efforts to improve maternal and child health more effectively.